International legal treatment of war - Mrkić Slavko (Međunarodni Problemi, 2009)
In this paper, the author presents and analyses various attempts made by the factors in the international community to define the rules of behavior in waging war as a means of communication among states in resolving their mutual problems. Presenting first the history (several centuries long) of attempts to restrain war waging the author focuses on the endeavors of the League of Nations in the period between the two world wars as well as on the creation of regulations by the United Nations after World War II. The author points out that the United Nations has built a comprehensive system of waging war restraint that, among other things, not only prohibits aggressive war waging, but also any use of armed force or threat of use of force. Some forms of military interventions could be taken only within the UN corresponding procedure. In spite of the fact that the treatment of war is regulated by the law within UN, it is present in the contemporary world as a result of the existing political and economic relations. As the author concludes, war and force keep on being used in practice, sometimes in a very violent way. Thus, they violate the provisions of international law that regulates the rules and treatment of war in international relations. .